Cell-derived vesicles exposing coagulant tissue factor in saliva - Berckmans, René J.; Sturk, Auguste; van Tienen, Laurens M.; Schaap, Marianne C.L.; Nieuwland, Rienk (Blood, 2011)
On vascular damage, coagulation is initiated by extravascular tissue factor (TF). Intravascular TF, which is present on circulating cell-derived vesicles, is noncoagulant under physiologic conditions but prothrombotic under pathologic conditions. Human saliva triggers coagulation, but the mechanism and physiologic relevance are unknown. Because saliva is known to contain TF, we hypothesized that this TF may also be associated with cell-derived vesicles to facilitate coagulation when saliva directly contacts blood. The saliva-induced shortening of the clotting time of autologous plasma and whole blood from healthy subjects (n = 10) proved TF-dependent. This TF was associated with various types of cell-derived vesicles, including microparticles and exosomes. The physiologic function was shown by adding saliva to human pericardial wound blood collected from patients undergoing cardiac surgery. Addition of saliva shortened the clotting time from 300 ± 96 to 186 ± 24 seconds (P = .03). Our results show that saliva triggers coagulation, thereby reducing blood loss and the risk of pathogens entering the blood. We postulate that our reflex to lick a wound may be a mechanism to enable TF-exposing vesicles, present in saliva, to aid in the coagulation process and thus protect the organism from entering pathogens. This unique compartmentalization may be highly conserved because also animals lick their wounds.